2019
DOI: 10.1017/pasa.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Origins Space Telescope: Predictions for far-IR spectroscopic surveys

Abstract: We illustrate the extraordinary potential of the (far-IR) Origins Survey Spectrometer (OSS) on board the Origins Space Telescope (OST) to address a variety of open issues on the co-evolution of galaxies and AGNs. We present predictions for blind surveys, each of 1000 h, with different mapped areas (a shallow survey covering an area of 10 deg 2 and a deep survey of 1 deg 2 ) and two different concepts of the OST/OSS: with a 5.9 m telescope (Concept 2, our reference configuration) and with a 9.1 m telescope (Con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 112 publications
1
25
0
Order By: Relevance
“…In this paper we shown that the data already imply interesting constraints on the IMF of high-z dusty galaxies. Forthcoming or planned sub-mm spectroscopic surveys, such as those with the Cerro Chajnantor Atacama Telescope (CCATprime; Stacey et al 2018) or with the Origins Space Telescope (OST; Leisawitz et al 2018;Bonato et al 2019), will shed light on this issue. GdZ acknowledges financial support by ASI/INAF Agreement 2014-024-R.0 for the Planck LFI activity of Phase E2.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we shown that the data already imply interesting constraints on the IMF of high-z dusty galaxies. Forthcoming or planned sub-mm spectroscopic surveys, such as those with the Cerro Chajnantor Atacama Telescope (CCATprime; Stacey et al 2018) or with the Origins Space Telescope (OST; Leisawitz et al 2018;Bonato et al 2019), will shed light on this issue. GdZ acknowledges financial support by ASI/INAF Agreement 2014-024-R.0 for the Planck LFI activity of Phase E2.…”
Section: Discussionmentioning
confidence: 99%
“…Strongly lensed galaxies detected by CMB experiments will be obvious targets for the next generation Very Large Array (ngVLA) that will provide accurate estimates of the molecular outflow masses and mass loss rates up to z 4 [57]. The proposed NASA flagship Origins Space Telescope [OST; 58,59] would detect molecular, neutral, and warm ionized phases of outflows up to higher redshifts, although with a spatial resolution lower than ngVLA. AGN-driven outflows also produce a bubble of hot gas, potentially detectable via its Sunyaev-Zeldovich effect [SZE; 60,61].…”
Section: Astrophysics and Cosmography With Strong Lensingmentioning
confidence: 99%
“…The line-L IR relations obtained by Bonato et al (2019) are based on observations of dusty galaxies, for which the unabsorbed fraction of the emission from young stars is small, so that L IR is a measure of the total SFR. One might wonder whether the line luminosities are primarily related to L IR or to the SFR and an answer was provided by De Looze et al (2014).…”
Section: Line-detection Limitsmentioning
confidence: 99%
“…Based on these results, following Bonato et al (2019) we assume that the luminosity of FIR fine-structure lines primarily correlates with the SFR. Thus, the relations derived by Bonato et al (2019) allow us to estimate the values of SFR as a function of z corresponding to the 5 σ line-detection limits listed in Table 1. The results are shown in Fig.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation